COCONUT PRODUCTS AND THEIR DIVERSIFICATION INDIAN EXPIERIENCE - P.K. THAMPAN (International Coconut Community, 1991)
The primary processing of coconut products is a popular activity in the major coconut growing states of India. Traditionally, coconut is processed at the farm leve] for conversion into copra and for the extraction of coir fibre. This activity has promoted oil milling and coir processing which are, presently, the most popular coconut based industries in India. In some states, particularly in Kerala, toddy tapping and the production of toddy‑based alcoholic beverages, vinegar, jaggery etc. arc also important activities with significant contribution to the annual income of the concerned states. Apart from the traditional utilisation of coconut palm products, product diversification and byproduct utilisation have not received the required fillip in the past in the absence of appropriate R and D support. The importance of developing viable technologies for the efficient utilisation of all the products of the palm both at the primary and secondary stages, has received recognition only for a short period during the early sixties and, subsequently, during the eighties after the Coconut Development Board was established. The recent achievements made in the development of appropriate technologies which have proved to be technically and economically viable related to the production of milk/cream, edible flour, water based beverages and other miscellaneous food and non food products.